Non-aqueous synthesis of hexagonal ZnO nanopyramids: Gas sensing properties - Muhammad Z., Ahmad; Jin, Chang; Muhammad Syarhabil, Ahmad, Dr.; Waclawik, Eric R., Assoc. Prof. Dr.; Wlodarski, W., Prof. (Elsevier B.V., 2013)
Link to publisher's homepage at http://www.elsevier.com/